A Hydrogen‐Bonded Cyanide‐Bridged [Co2Fe2] Square Complex Exhibiting a Three‐Step Spin Transition. Issue 2 (7th December 2016) - Nihei, Masayuki; Yanai, Yuta; Hsu, I.‐Jui; Sekine, Yoshihiro; Oshio, Hiroki
Abstract: Co‐crystallization of a cyanide‐bridged tetranuclear complex [Co2 Fe2 ] with 4‐cyanophenol (CP) gave a hydrogen bonding donor–acceptor system, [Co2 Fe2 (bpy*)4 (CN)6 (tp*)2 ](PF6 )2 ⋅2 CP⋅8 BN (1 ).1 exhibited a three‐step phase transition between HT, IM1, IM2, and LT phases upon temperature variation. Variable temperature magnetic measurements and structural analyses revealed that the three‐step spin transition is caused by electron‐transfer‐coupled spin transitions (ETCSTs) accompanied with alteration of the hydrogen bonding interactions. Abstract : Waltzing along : A three‐step spin transition is observed in a hydrogen bonding donor–acceptor system composed of a spin‐transition‐active square complex [Co2 Fe2 ] and aromatic hydrogen bonded donor molecules. The stabilization of the intermediate phases is caused by a dynamic alteration of hydrogen bonding interactions coupled to spin‐transition behavior.